Intertrochanteric fractures and mortality in elderly patients - Tsitko, Hanna; Dudzińska, Paulina; Milanowska, Małgorzata; Grudzińska, Aleksandra; Jarosz, Dominika (Journal of Education, Health and Sport, 2022)
The aim of the following article was to provide an overview of the medical knowledge on the correlation of intertrochanteric fractures of the femur and mortality in the elderly population. Due to the fact that life expectancy has increased, we can observe an increasing trend of hip fractures. There are about 20,000 fractures of the proximal end of the femur treated in Poland and 300,000 patients in the United States annually. It is estimated that the upward trend of fractures can be traced to 2050 with an increase of +1% per year. There are expected to be 6 million cases per year worldwide according to International Osteoporosis Foundation. The most frequently early mortality related factors are biodemographic factors - age and gender. The majority - 75% of those treated fractures are female. Also, the risk of fracture of the proximal end of the femur in women over 50 years is almost 20%, and by the age of 80 it reaches 30%. Although among women the risk of fracture is higher, mortality is lower than man who experienced the same fracture. Other predictors of poor functional outcomes and early mortality factors for patients with hip fracture besides age and gender, are clinical factors, such as time spent waiting for surgery or comorbidities. Knowing those factors, we can try to avoid some complications. Each surgeon has to remember about a multidisciplinary care protocols, which are made to improve healthcare, shorten length of hospital stay, and decrease mortality in hip‐fracture‐operated patients. Also, it is significant to select proper surgical methods depending on the fracture complexity. This article was written based on analyzing data available in publications in Pubmed and Google Scholar databases.